Measuring Theory of Mind in Adolescents With Language and Communication Problems: An Ecological Perspective - Smit, Lidy; Knoors, Harry; Rabeling-Keus, Inge; Verhoeven, Ludo; Vissers, Constance (Frontiers in Psychology, 2022)
We tested if the newly designed ToMotion task reflects a single construct and if the atypical groups differ in their performance compared to typically developing peers. Furthermore, we were interested if ToMotion maps a developmental sequence in a Theory of Mind (ToM) performance as exemplified by increasing difficulty of the questions asked in every item. The sample consisted of 13 adolescents that have been diagnosed with a developmental language disorder (DLD) and 14 adolescents that are deaf or hard of hearing (DHH). All of these adolescents were in special schools for secondary vocational education. The control group existed of 34 typical developing adolescents (TD) who were in regular intermediate vocational education, ranging from level 2 to 4. The ToMotion, available in a spoken Dutch version and in a version in Sign Language of the Netherlands (SLN), was used to map ToM abilities. An attempt has been made to fill the gap of missing studies of ToM in adolescents by developing a new measuring instrument. In conclusion, assessing ToM with the ToMotion results in a picture that DHH adolescents score lower than TD peers. However, their scores are as consistent as those of the TD peers. The picture of DLD adolescents is the reverse. They show no differences in ToM scores, but seem to be somewhat more inconsistent compared to TD peers. We provide a discussion on those results and its implications for future research. What this paper adds? The current study introduces a new visual Theory of Mind (ToM) task, ToMotion, designed specifically to assess ToM in adolescents in an ecologically valid way and adapted to the needs of adolescents with language and communication difficulties.